Cholangioscopy-guided lithotripsy for difficult bile duct stone clearance in a single session of ERCP: results from a large multinational registry demonstrate high success rates - Maydeo, Amit P.; Rerknimitr, Rungsun; Lau, James Y.; Aljebreen, Abdulrahman; Niaz, Saad K.; Itoi, Takao; Ang, Tiing Leong; Reichenberger, Jörg; Seo, Dong Wan; Ramchandani, Mohan K.; Devereaux, Benedict M.; Lee, Jong Kyun; Goenka, Mahesh K.; Sud, Randhir; Nguyen, Nam Q.; Kochhar, Rakesh; Peetermans, Joyce; Goswamy, Pooja G.; Rousseau, Matthew; Bhandari, Surya Prakash; Angsuwatcharakon, Phonthep; Tang, Raymond S. Y.; Teoh, Anthony Y. B.; Almadi, Majid; Lee, Yun Nah; Moon, Jong Ho; the SpyGlass AMEA Registry Group (Endoscopy, 2019)
Background Peroral cholangioscopy (POCS) can be useful for difficult bile duct stone clearance. Large prospective multinational data on POCS-guided lithotripsy for clearing difficult bile duct stones in a single session of endoscopic retrograde cholangiopancreatography (ERCP) are missing.Methods Patients with difficult bile duct stones (defined as one or more of: largest stone diameter ≥ 15 mm, failed prior attempt at stone clearance, impacted, multiple, hepatic duct location, or located above a stricture) were enrolled at 17 centers in 10 countries. The principal endpoint was stone clearance in a single ERCP procedure using POCS.Results 156 patients underwent 174 sessions of POCS-guided electrohydraulic or laser lithotripsy. Stone clearance had failed in a previous ERCP using traditional techniques in 124/156 patients (80 %), while 32 /156 patients (21 %) were referred directly to POCS-guided therapy based on preprocedural assessment of the difficulty of stone clearance. In 101/156 patients (65 %), there were impacted stones. POCS-guided stone clearance was achieved in a single POCS procedure in 125 /156 patients (80 %, 95 % confidence interval [CI] 73 % – 86 %), and was significantly more likely for stones ≤ 30 mm compared with > 30 mm (odds ratio 7.9, 95 %CI 2.4 – 26.2; P = 0.002). Serious adverse events occurred in 3/156 patients (1.9 %, 95 %CI 0.4 % – 5.5 %), and included pancreatitis, perforation due to laser lithotripsy, and cholangitis (n = 1 each), all resolved within 1 week.Conclusion POCS-guided lithotripsy is highly effective for clearance of difficult bile duct stones in a single procedure and successfully salvages most prior treatment failures. It may also be considered first-line therapy for patients with difficult choledocholithiasis to avoid serial procedures.